NPY antagonism reduces adiposity and attenuates age‐related imbalance of adipose tissue metabolism. Issue 12 (9th September 2014) - Park, Seongjoon; Fujishita, Chika; Komatsu, Toshimitsu; Kim, Sang Eun; Chiba, Takuya; Mori, Ryoichi; Shimokawa, Isao
Abstract : An orexigenic hormone, neuropeptide Y (NPY), plays a role not only in the hypothalamic regulation of appetite, but also in the peripheral regulation of lipid metabolism. However, the intracellular mechanisms triggered by NPY to regulate lipid metabolism are poorly understood. Here we report that NPY deficiency reduces white adipose tissue (WAT) mass and ameliorates the age‐related imbalance of adipose tissue metabolism in mice. Gene expression involved in adipogenesis/lipogenesis was found to decrease, whereas proteins involved in lipolysis increased in gonadal WAT (gWAT) of NPY‐knockout mice. These changes were associated with an activated SIRT1‐ and PPARγ‐mediated pathway. Moreover, the age‐related decrease of de novo lipogenesis in gWAT and thermogenesis in inguinal WAT was inhibited by NPY deficiency. Further analysis using 3T3‐L1 cells showed that NPY inhibited lipolysis through the Y1 receptor and enhanced lipogenesis following a reduction in cAMP response element‐binding protein (CREB) and SIRT1 protein expression. Therefore, NPY appears to act as a key regulator of adipose tissue metabolism via the CREB‐SIRT1 signaling pathway. Taken together, NPY deficiency reduces adiposity and ameliorates the agerelated imbalance of adipose tissue metabolism, suggesting that antagonism of NPY may be a promising target for drug development to prevent age‐related metabolic diseases.—Park, S., Fujishita, C., Komatsu, T., Kim, S. E., Chiba, T., Mori, R., Shimokawa, I., NPY antagonism reduces adiposity and attenuates age‐related imbalance of adipose tissue metabolism. FASEB J. 28, 5337–5348 (2014). www.fasebj.org